PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN KAS, DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2023 - Mutmainna, Mutmainna; Darwis, Darwis; Semaun , Syahriyah; Sahrani, Sahrani (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
The study was conducted to test whether there is an effect of working capital turnover, cash turnover and accounts receivable turnover on Return On Asset (ROA) of 7 automotive and component sub-sector companies for the period 2021-2023.This study uses a quantitative method with an associative quantitative approach that uses the field research type. Data processing using SPSS version 22. The data analysis technique uses classical assumption testing, multiple linear analysis and hypothesis testing.The results of the study obtained 1) Working Capital Turnover (X1) has a probability value (Sig.) Of 0.000 <0.05 and has a t count of 6.758> t table 2.10982 which means that Working Capital Turnover (X1) has a positive effect on Profitability (Y). 2) Cash Turnover (X2) has a probability value (Sig) of 0.118 > 0.05 and has a calculated t of -1.646 < t table 2.10982 which means that Cash Turnover (X1) has a negative effect on Profitability (Y). 3) Receivables Turnover (X3) has a probability value (Sig) of 0.047 < 0.05 and has a calculated t of -2.142 < t table 2.10982 which means that Receivables Turnover (X1) has a positive effect on Profitability (Y). 4) Working Capital Turnover (X1), cash turnover (X2) and Accounts Receivable Turnover (X3) have a probability (Sig) of 0.000 < 0.05 and show a calculated f value of 15.489 > f table 3.16, which means they simultaneously influence Profitability (Y).